2012
DOI: 10.1007/s11356-012-1401-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding properties of extracellular polymeric substances extracted from anaerobic granular sludges

Abstract: Extracellular polymeric substances (EPS) were extracted from four anaerobic granular sludges with different procedures to study their involvement in biosorption of metallic elements. EPS extracts are composed of closely associated organic and mineral fractions. The EPS macromolecules (proteins, polysaccharides, humic-like substances, nucleic, and uronic acids) have functional groups potentially available for the binding of metallic elements. The acidic constants of these ionizable groups are: pKa1 (4-5) corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…The second zone was located at pH 6.4, which was attributed to thiol or phosphate groups. The third buffering zone was located at pH 9.6, which was attributed to amino or hydroxyl groups (D'Abzac et al, 2013). The peaks indicated a maximum variation in pH corresponding to the equivalence points, and the local minima indicated a minimum variation in pH, which is indicative of buffering (Braissant et al, 2007).…”
Section: Potentiometric Titrationmentioning
confidence: 97%
See 2 more Smart Citations
“…The second zone was located at pH 6.4, which was attributed to thiol or phosphate groups. The third buffering zone was located at pH 9.6, which was attributed to amino or hydroxyl groups (D'Abzac et al, 2013). The peaks indicated a maximum variation in pH corresponding to the equivalence points, and the local minima indicated a minimum variation in pH, which is indicative of buffering (Braissant et al, 2007).…”
Section: Potentiometric Titrationmentioning
confidence: 97%
“…It was concluded that Cu 2+ and Zn 2+ had greater binding affinity for the functional groups of polysaccharides in the EPS. For example, Cu 2+ binds the carboxyl groups of EPS, while carboxyl and phosphoric functional groups are involved in the binding between Pb 2+ and EPS (Li and Yu, 2014;D'Abzac et al, 2013).…”
Section: Effects Of Heavy Metals On Srb Activity and Eps Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…-------------------- Table 1 2.1.2 EPS extraction and characterization EPS extraction procedures were carried out according to the methods developed by [18].…”
Section: Origin Of Sludgementioning
confidence: 99%
“…For protein content, the protocol established by [20] was used. For analysis of the mineral composition, protocol from [18] is followed: 3 mL of EPS sample was submitted acid digestion; then digestion was performed with a microwave 3000 (Anton Paar) The metal concentrations in the acid-digested samples were quantified using an atomic absorption spectrometer (Varian Zeeman ASS 800) and inductively coupled plasma optical emission spectrometry (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS) (by ACME Analytical Laboratory Itd. (Vancouver, Canada)) for EPS from GS Sm and GS Ee respectively.…”
Section: Origin Of Sludgementioning
confidence: 99%